Migration and religion in East Asia : North Korean migrants' evangelical encounters - Jung, Jin-Heon, 1969- (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2015)
"Since the mid-1990s when North Korea was gripped by a devastating famine, increasing numbers of North Korean migrants have been crossing the Sino-North Korean border en route to Seoul, South Korea, in search of a better life. Based on fieldwork conducted in Seoul and Northeast China, Migration and Religion in East Asia sheds light on North Korean migrants' Christian encounters and conversions throughout the process of migration and settlement. Focusing on churches as primary contact zones, it highlights the ways in which the migrants and their evangelical counterparts both draw on and contest each others' envisioning of a reunified Christianized nation-state. Analysing the intersections between religious and political conversion and physical migration, it scrutinises cultural understandings of identity politics, religio-political aspirations, competing discourses on humanitarianism, and freedom in both religious and national terms in the context of late-Cold War Korea"--
Machine generated contents note: -- 1. Introduction: North Korean Migrants and Contact Zones -- 2. The Politics of South Korean Evangelical Nationalism -- 3. Perilous Crossing: North Koreans' Christian Encounters in the Sino-North Korean Border Area -- 4. Heroes to Regular Citizens: The Politics of North Korean Migrants Subjectivities -- 5. Ideal Body, True Christians: The Freedom School -- 6. Narrativization of Christian Passage: From Refugees to God's Warriors -- 7. Conclusion: Free to Be.
Includes bibliographical references and index.
Keywords: Christianity -- Korea; Evangelicalism -- Korea; Emigration and immigration -- Religious aspects -- Christianity -- History -- 21st century; Emigration and immigration -- Political aspects -- History -- 21st century; Korea -- Church history -- 21st century; Korea -- Emigration and immigration -- History -- 21st century; Korea; 2000 - 2099